2022
DOI: 10.2991/ahsr.k.220303.007
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of α-Mangosteen on Runt-Related Transcription Factor 2 and Tartrate-Resistant Acid Phosphatase 5b Expressions on Bone Remodeling in Periodontitis (An Experimental Research on Wistar Rats)

Abstract: The alteration of supporting structures of the teeth in periodontitis results from the complex interaction between colonies of microorganisms and the immune-inflammatory host response. α-mangosteen contains xanthone which has antioxidant, anti-inflammatory, anti-fungal, and osteoinductive properties and has the potential as an alternative treatment to promote bone remodeling of the damaged bone in periodontitis. This study aims to investigate the effect of α-mangosteen on RUNX2, and TRAP5b. Forty-eight Wistar … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…11 12 The effect is similar to α-mangosteen, which is able to stimulate some growth factors like tumor growth factor-β, 13 and TRAP5b 14 and also inhibit the growth of etiological bacteria 15 16 and RUNX2. 14…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…11 12 The effect is similar to α-mangosteen, which is able to stimulate some growth factors like tumor growth factor-β, 13 and TRAP5b 14 and also inhibit the growth of etiological bacteria 15 16 and RUNX2. 14…”
Section: Introductionmentioning
confidence: 94%
“…The finding showed that EGCG inhibits the process of alveolar bone damage through RANKL, 10 TNF-α, 11 and increases osteoprotegerin (OPG), 10 RANK, 10 11 and IL-10. 11 12 The effect is similar to α-mangosteen, which is able to stimulate some growth factors like tumor growth factor-β, 13 and TRAP5b 14 and also inhibit the growth of etiological bacteria 15 16 and RUNX2. 14…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation